Grief in childhood: the constitution of childhood loss and death (2019)
This research which is focused on how children assumethe process of grieving has two goals. First, it aims tounderstand emotional reactivity when it comes downto those defense mechanisms related to the loss of aclose relative. Then, it focuses on understanding howgirls build the idea of death when they lose a familymember.Regarding methodology, this is a qualitative studywith a hermeneutical approach and psychoanalysis,which has been used as a theoretical reference. Thiswork involved the study of two young girls between 4-6 years old who lost one of their parents. Otherfamily members were also interviewed, and variousassessment techniques such as: interviews, projectivetests and one-on-one meetings were used as well.Therefore, the results indicate that grief in the infantstage is a process that generates displeasure, linked tothe forced abandonment of the investiture placed inthe beloved object, and the helplessness projected ina psyche in constitution can be almost intolerable.Within the emotional manifestations associated withthe loss, there are nightmares with a repetitive dreampattern, memories and daydreams with the deceasedperson; and the presence of regressive mechanismsafter the relative’s death.Death is taken as a transitory event; therefore, deathcan be played without the definitive absence ofthe object of love being understood. The meaningof death derives, also, from family traditions andrelationships with the other. The girls’ exposure toburial rituals seeks to eliminate from the subjectivitythe plot of death as a transitory game, markingthe idea of the material absence of the loved one.However, assimilating absence as a definitive andnon-transitory act is a complex psychic process thatgoes beyond these rituals.